THE IMPACT OF ARCHAEOLOGICAL RECORDING ON THE STUDY OF METAL ARTEFACTS. MYCENAE 1939: A CASE STUDY. (December 2022) - Aulsebrook, Stephanie
Abstract : Aegean Archaeology is one of the oldest branches of prehistoric archaeological scholarship, and many important settlements and cemeteries, such as those at Mycenae, were excavated before the development of more advanced recording techniques that we take for granted today. Nevertheless, the significance of these legacy data as a source of knowledge means we must still find ways to integrate them into our interpretations, despite their limitations. To derive the most robust results possible, it is important to understand exactly what types of impact these earlier recording strategies may have had on our perception of their findings. Yet this type of investigation is rare, meaning that in many cases we know more about the repercussions of taphonomy and the social practices of past societies on the archaeological record than those caused by the actions of our own predecessors. In preparation for a holistic study of all aspects of the use of metals at the Late Bronze Age site of Mycenae, this paper details the exploration of the recording processes in place during the 1939 excavation season. This has been identified as an ideal case study for examining recording strategies because its organisational structure gave each trench supervisor a great deal of individual freedom. Concentrating on their consequences for metal artefacts in particular, each stage of the recording process, in the field, in the museum and in publications, is discussed, as is the aftermath of the Second World War.